6-2(4-4x)=0

Simple and best practice solution for 6-2(4-4x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-2(4-4x)=0 equation:


Simplifying
6 + -2(4 + -4x) = 0
6 + (4 * -2 + -4x * -2) = 0
6 + (-8 + 8x) = 0

Combine like terms: 6 + -8 = -2
-2 + 8x = 0

Solving
-2 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 8x = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 8x = 0 + 2
8x = 0 + 2

Combine like terms: 0 + 2 = 2
8x = 2

Divide each side by '8'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 35x^2+49x=168 | | 5(w-4)-(1-8w)=12w | | 35x^2+49=168x | | 48-2x=5x+7 | | -(-2+n)=-4+11n | | 35x^2+49=168 | | 4y^2-4y-24=0 | | 3-2(8x+4)=5 | | 6-(2x-6)=7-3x | | -4x+(4+6x)=10 | | 5x+2=25+50x | | 4t^2-13t-35=0 | | 3x^3-2x^2-3x-4= | | x^2+7x+3=3 | | 374+78x+4x^2=644 | | 287.64=9(0.05m+21.70+0.30(21.70)) | | -6-(4-b)=30 | | 3y+9x+5y= | | 9y-8=8y | | 0=-16t^2+75t-23 | | .4+7=7 | | -x+7=5x+11 | | 12t+4=16t-8 | | -7x+3-5x=3x-31+2x | | 7x+21=-21-3x | | 6-1.5x=24 | | 3ln(x)+2x=3ln(20)+ln(10) | | x(-13-x)=42 | | 4+12t=8-16t | | 3*ln(x)+2*x=3*ln(20)+ln(10) | | -6(x-4)=-3(x-2) | | -10x+1-7=-17x+7 |

Equations solver categories